Mottled dolomite in the lower Cambrian Longwangmiao formation in the Northern Sichuan Basin, South China - Xuefei Yang; Hao Tang; Junyi Zhang; Yao Du; Ruifeng Tang; Shuang Pan; Xiang Zhou; Yan Xu (Petroleum, 2024)
At the end of Early Cambrian time, the Sichuan basin (South China) was located in a wide carbonate platform, with hundreds of meters of carbonate deposited. The Longwangmiao Formation carbonate in Sichuan basin is partially to completely dolomitized, displaying a mottled texture in the northern area of the exposure. The mottled dolomitic limestone developed parallel to bedding, with shape irregular boundaries with limestone that has not been dolomitized. The mottled dolomite is composed of powder crystalline and finely crystalline dolomite, while the matrix limestone is composed of micritic calcite. the isotopic composition of mottled dolomite (δ13C = +0.29‰PDB, δ18O = −1.15‰PDB) is similar to that of micrite calcite (δ13C = −0.49‰PDB, δ18O = −1.45‰PDB). Both isotopic values and trace element data indicate that the dolomitized fluid is originated from sea water. Some beds contain gypsum pseudomorphs and mud cracks, indicating a shallow and evaporative environment with local high salinity during deposition. Dolomitization likely took place early, in part as a result of sea water salinity concentration. Trace fossils thalassinoides horizontalis, thalassinoides callianassa and planolites developed in the Longwangmiao Formation, and the sharp edges of mottled dolomite are similar to these trace fossils. The beds are intensely bioturbated. In the burrow network, the sediments and burrow fill were coarse and loose with little clay, and it is interpreted here as being easier to be dolomitized than the surrounding sediments. Partial dolomitization is thus interpreted to have occurred in the burrow system, and the degree of dolomitization was related to the degree of bioturbation, which is controlled by the trace-making creatures.